Evaluation of Color Stability of 3D Printing Resins After Exposure to Various Colorants: an in vitro study - Verniani, G.; Cagidiaco, E. F.; Pollis, M.; Haichal, W. S.; Casucci, A. (Journal of Osseointegration, 2025)
Purpose. This study investigates the color stability of four types of 3D printing resins: TempPrint (TP) (GC), Varseo Smile Teeth (VST) (Bego), TrinQ (TQ)(Bego), and V-Print(VP) (Voco) when exposed to various colorants over a 30-day period. Methods. A total of 200 disk-shaped specimens (10 mm × 2 mm) were printed using a DLP printer and exposed to four colorants: wine, Coca-Cola, tea, coffee and distilled water. Color changes were measured at 7, 15, and 30 days and total color differences (ΔE) were calculated. Results. The results revealed significant discoloration across all resins, with wine and coffee inducing the most pronounced color changes. TP (GC) demonstrated the least discoloration in all solutions, particularly in water and Coca-Cola. VST(Bego) showed the highest degree of discoloration, especially in wine and coffee, with ΔE values reaching 20.54 after 30 days of immersion in coffee. TQ (Bego) and VP (Voco) exhibited intermediate levels of discoloration, with coffee causing the most severe color changes. Statistical analysis indicated significant differences in color stability between the resins, with wine and coffee causing more discoloration. Clinical significance. These findings suggest that while all resins undergo color change when exposed to common beverages, the extent of discoloration varies based on resin composition, highlighting the need for material selection based on expected environmental exposure in practical applications.